The reference to Timaeus in Physics IV 2 - Casnati, María Gabriela (2013)
In this paper, we discuss some possible readings of Physics IV 2, where Aristotle identifies the Platonic ???? of the Timaeus with ???, ???????????? and ??????????. We will study common features that bring the receptacle of the Timaeus closer to Aristotelian matter and space, and that make it natural for Aristotle to identify ???? with matter. However, we will try to show that, in spite of the similarities between the receptacle and what Aristotle understands for place and matter, the mechanics of appropriation of the Platonic text that the Stagirite operates, forcing an equivalence with his own technical terms, possibly implies a distortion that, in the end, does not do justice to the formulations of the teacher.